Language Styles and Learning Motivation Changes in Instagram Captions: A Case of Three International Students - Vidya Mukti Cakraningrum; Widhiyanto (Universitas Islam Negeri Palopo, 2025)
This study analyzes the changes in language style and English learning motivation reflected in 181 Instagram captions from three international students pursuing higher education in Indonesia. The analysis is based on Martin Joos's theory of language styles and Dörnyei's L2 Motivational Self System. This qualitative descriptive research focuses on comparing captions from the period before and during their study in Indonesia. The findings indicate a significant shift. Prior to their studies, the dominant language style was casual (41.41%), and motivation was rarely expressed (2.02%), categorized primarily as L2 Learning Experience. However, during their time abroad, language styles became more varied. While the casual style remained dominant (39.23%), the use of the consultative style also increased (23.20%), suggesting an adaptation to audience and communicative goals. Motivational expressions also increased significantly, especially L2 Learning Experience (19.34%), followed by Ideal L2 Self (6.08%) and Ought-to L2 Self (2.21%). These changes highlight the strong influence of social, academic, and personal development on language use and motivational expression on social media. The findings support Dörnyei's assertion that language motivation is not static but evolves in response to a learner's experiences. This research contributes to the literature on digital discourse and language learning motivation in the context of English education.